Delovna terapija pri pacientih z miopatijo kritično bolnih po COVID-19 - Prosič, Zdenka (Rehabilitacija (Ljubljana), 2021)
Background: Approximately 20 % of patients with COVID-19 require hospitalisation in the intensive care unit. Critical illness myopathy (CIM) often develops due to respiratory failure and consequent artificial ventilation. As a result, patients face problems in different areas of human occupa-tion. The purpose of our study was to determine whether patients with CIM after COVID-19 progress in the same way in occupational therapy as patients with CIM with other causes. Methods: Nine patients with CIM caused by other diseases and 10 patients with CIM after COVID-19 were included in the study. They were assessed with standardised measurement tools: the Canadian Occupational Performance Measure (COPM), the Goal Attainment Scaling (GAS) and the Functional Independence Measure (FIM). Results: According to COPM, patients in both groups rated their performance and satisfaction similar-ly. The starting point for the GAS scale was -2 in both groups. The COVID-19 CIM group progressed slightly better, but the difference between the groups was not statistically signifi-cant. There was a statistically significant difference between the initial and final assessment of the overall FIM scale within the first (p<0.001) and second group (p<0.015). On average, the first group progressed by 24 points and the second by 33.2 points. The difference between the groups was not statistically significant. Conclusion: All patients made statistically significant progress during rehabilitation. When comparing pa-tients after myopathy with those who also experienced COVID-19, there were no essential differences in the outcomes of occupational therapy treatment.
Keywords: assessment; COVID-19; critical illness myopathy; delovna terapija; miopatija kritično bolnega; Occupational Therapy; ocenjevanje; rehabilitacija; rehabilitation